Association between the CD14−260C>T gene polymorphism and susceptibility to myocardial infarction: Evidence from case−control studies. (11th June 2019) - Zhao, Enfa; Wang, Chaoliang; Xie, Hang; Du, Yajuan; Zhang, Yushun
Abstract: Numerous published studies have investigated the relationship between the CD14−260C>T (rs2569190) polymorphism and the risk of myocardial infarction (MI). However, the results are still conflicting and inconclusive. Potentially eligible published articles were searched in four databases including PubMed, Web of Science, EMBASE and Chinese Biomedical Database (CBM). The odds ratio (OR) with its 95% confidence interval (CI) was used to estimate the strength of the associations. Thirteen papers including 17 case–control studies were included, reporting a total of 6, 443 MI patients and 6, 315 controls. A significant increase in overall MI susceptibility was identified in the homozygote model. In the subgroup analysis, with respect to the type of MI, a significantly increasing acute MI susceptibility was found in the homozygote model. In the subgroup analysis for ethnicity, a significant increased susceptibility was found in Asian populations in allele, homozygote, recessive and dominant models. However, no significant association was found among Caucasian populations. In conclusion, there may be a moderate association between the CD14−260C>T polymorphism and acute MI susceptibility. This association may be different between ethnicities with the CD14−260C>T polymorphism being a risk factor for myocardial infarction in Asian populations.